Comparison of end-to-side versus side-to-side anastomosis in upper limb arteriovenous fistula in hemodialysis patients: A systematic review and meta-analysis - Zhou, Yu; Wu, Hongyan (Frontiers in Surgery, 2023)
Objective: It is currently unclear if the anastomosis technique impacts the patency of upper arm arteriovenous fistula (AVF) in hemodialysis patients. This review compared outcomes of end-to-side and side-to-side anastomosis for AVF fistula in hemodialysis patients. Methods: PubMed, CENTRAL, Web of Science, and Embase were searched for all types of studies published between 1st January 2000 to 3rd September 2022. Patency rates at 6 months, 12 months, maturation time, and complications were compared between ETS and STS groups. Results: Sixteen studies including six randomized controlled trials (RCTs) were included. Meta-analysis showed no difference in patency rates between ETS and STS group at 6 months (OR: 1.15 95% CI: 0.72, 1.83 I2=52% p=0.56) but better patency with STS at 12 months (OR: 0.63 95% CI: 0.41, 0.95 I2=21% p=0.03). The difference was non-significant in a subgroup analysis of RCTs and non-RCTs. In the absence of distal vein ligation in the STS group, the ETS group had significantly better patency at 6 months but with distal vein ligation, STS had higher patency at 12 months. Meta-analysis demonstrated no difference in maturation time between the two groups (MD: 0.10 95% CI: 0.29, 0.49 I2=89% p=0.61). Only a descriptive analysis of complications could be carried out with no major difference. Conclusion: Our review demonstrates that the STS anastomosis technique with distal vein ligation may result in significantly better patency rates as compared to the standard ETS technique. Data for complication rates are scarce and varied but without any significant differences between the two techniques.